2015
DOI: 10.1007/s00125-015-3523-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the receptor for advanced glycation endproducts (RAGE) in retinal vasodegenerative pathology during diabetes in mice

Abstract: Aims/hypothesisThe receptor for AGEs (RAGE) is linked to proinflammatory pathology in a range of tissues. The objective of this study was to assess the potential modulatory role of RAGE in diabetic retinopathy.MethodsDiabetes was induced in wild-type (WT) and Rage−/− mice (also known as Ager−/− mice) using streptozotocin while non-diabetic control mice received saline. For all groups, blood glucose, HbA1c and retinal levels of methylglyoxal (MG) were evaluated up to 24 weeks post diabetes induction. After mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 43 publications
5
60
0
Order By: Relevance
“…68,69 One possible mechanism whereby ACE2 overexpression attenuates the diabetes-associated increase of macrophage/ microglial cells ( Figure 5) is attributable to the ability of Ang(1-7) to antagonize AGTR1s (which are expressed on microglia). AGTR1 blockade with valsartan effectively decreased microglial density in a rodent model of DR. 70 Consistent with our findings, McVicar et al 65 found a significant increase of F4/80 þ microglia in the retina when compared with nondiabetic controls, after 3 and 6 months of diabetes in mice. Similarly, Muther et al 71 observed a regular distribution of F4/80 þ in the healthy mouse retina.…”
Section: Retinal Overexpression Of Ace2 May Suppress Proinflammatory supporting
confidence: 91%
See 1 more Smart Citation
“…68,69 One possible mechanism whereby ACE2 overexpression attenuates the diabetes-associated increase of macrophage/ microglial cells ( Figure 5) is attributable to the ability of Ang(1-7) to antagonize AGTR1s (which are expressed on microglia). AGTR1 blockade with valsartan effectively decreased microglial density in a rodent model of DR. 70 Consistent with our findings, McVicar et al 65 found a significant increase of F4/80 þ microglia in the retina when compared with nondiabetic controls, after 3 and 6 months of diabetes in mice. Similarly, Muther et al 71 observed a regular distribution of F4/80 þ in the healthy mouse retina.…”
Section: Retinal Overexpression Of Ace2 May Suppress Proinflammatory supporting
confidence: 91%
“…These cells were increased in streptozotocin-control by approximately threefold to fourfold compared with nondiabetic or ACE2-treated diabetic, consistent with previous findings. 65,66 Also consistent with our findings (Figure 5), DR has generally been found to be associated with increased microglia number near retinal vasculature in the inner retinal layers and in the outer plexiform layer, 25,67 normally localizing anterior to the outer nuclear layer. 52 This organization within the ganglion cell layer is consistent with the finding, in individuals with DR, that microglia accumulate around regions of vascular damage 25 and that vascular lesions in the diabetic retina are nonuniform in distribution.…”
Section: Retinal Overexpression Of Ace2 May Suppress Proinflammatory supporting
confidence: 91%
“…Indirect evidence that the activation of Glo-1 might improve the neurovascular unit comes from studies using mice deficient in the receptor for AGEs (RAGE). McVicar et al [59] found that Rage (also known as Ager)-knockout mice accumulated less methylglyoxal in their retinas in association with a strong activation of Glo-1 and were protected against microglial activation and vasoregression, with a minor, non-significant effect on pericyte dropout. Beyond genetic control of Glo-1 activity, established drugs have shown Glo-1-modulating properties.…”
Section: Reactive Metabolites In Diabetic Retinopathymentioning
confidence: 99%
“…Advanced glycation end products account for many diabetes complications through their engagement to advanced glycosylation end productspecific receptor (AGER) (4)(5)(6). Inhibition of AGER is regarded as a therapeutic option to prevent diabetes complications (7). Despite an epidemiologic study that has demonstrated that AGER may be involved in liver injury and subsequent carcinogenesis (8), the exact roles of AGER in liver tumorigenesis are still unknown.…”
mentioning
confidence: 99%